18F-sodium fluoride and 18F-fluorodeoxyglucose positron emission tomography for assessment of aortic valve inflammation and calcification in patients with aortic stenosis - P. M. Murtazalieva (Российский кардиологический журнал, 2019)
Aim. To determine the inflammation and calcification activity in aortic stenosis (AS) by assessing the accumulation of 18F-FDG and 18F-NaF in the aortic valve; to study the relationship of the AS severity, aortic calcification and the accumulation of 18F-FDG and 18F-NaF. Material and methods. The study included 62 patients with asymptomatic AS (29 patients with tricuspid (TAV) and 33 with bicuspid (BAV) aortic valve), aged 40 to 70 years. The maximum flow rate at the aortic valve (Vmax) differs from 2,4 m/s to 4,5 m/s. The mean age of patients was 59,44±7,33 years, M:W 1:1. Patients with infective endocarditis and chronic rheumatic heart disease were excluded. The AS severity was assessed according to the standard protocol of transthoracic echocardiography with the use of Vivid 7 ultrasound system (GE,USA). All patients underwent combined positron emission tomography/computed tomography (PET/CT) of the aortic valve using the Discovery 710 system. Evaluation of calcification and inflammation activity of the aortic valve was performed using 8F-NaF and 18F-FDG PET/CT. A quantitative assessment of radiopharmaceuticals accumulation was carried out using uptake ratio indices. The calcium score was calculated using SmartScore 4.0 software.Results. Patients with TAV and BAV were comparable in severity of AS, the median Vmax was 2,9 [2,6; 3,4] m/s and 2,9 [2,3; 3,3] m/s, respectively. Also, TAV and BAV patients did not differ in calcification values (Agatston score 1088 [465; 2192] and 1128 [442; 2391] HU, respectively). The association of 18F-FDG accumulation and AS severity has not been established. At the same time, the association was found between the aortic valve peak velocity and the calcium score (r=0,57, p< 0,0001), as well as the 18F-NaF accumulation values — maximum, mean and maximum to mean (r=0,37, p=0,002; r=0,46, p=0,0001 and r=0,41, p=0,0008, respectively). No association between the accumulation of 18F-FDG and 18F-NaF (r=0,098, p=0,49) was found.Conclusion. It was found that the inflammation according to 18F-FDG PET/CT does not play a significant role in AS pathogenesis. At this time, 18F-NaF PET/CT is a reliable method for the AS diagnosis and valve calcification assessment. It can be used to evaluate the prognosis and effectiveness of therapy in TAV and BAV patients.